Wavelet transforms associated with the index Whittaker transform. (21st April 2021) - Prasad, Akhilesh; Maan, Jeetendrasingh; Verma, Sandeep Kumar
Abstract : The continuous wavelet transform (CWT) associated with the index Whittaker transform is defined and discussed using its convolution theory. Existence theorem and reconstruction formula for CWT are obtained. Moreover, composition of CWT is discussed, and its Plancherel's and Parseval's relations are also derived. Further, the discrete version of this wavelet transform and its reconstruction formula are given. Furthermore, certain properties of the discrete Whittaker wavelet transform are discussed.